Impacts of Transboundary Dust Transport on Aerosol Pollution in the Western Yangtze River Delta Region, China: Insights Gained From Ground‐Based Lidar and Satellite Observations. Issue 3 (15th March 2021) - Yang, Hao; Fang, Zhiyuan; Cao, Ye; Xie, Chenbo; Zhou, Tian; Wang, Bangxin; Xing, Kunming; Lolli, Simone
Abstract: Dust storms pose a serious threat to air quality and public health through large‐scale, long‐distance transport. In early April 2018, two severe dust storm events occurred in the Taklimakan and Gobi Deserts in northwestern China. The advected air‐masses containing dust traveled eastward over long distances reaching the western Yangtze River Delta region (WYRDR) with local PM10 peak concentrations of 190 and 410 μg/m 3 on April 6 and April 11, 2018, respectively. Satellite remote sensing and ground‐based lidar observations showed that the first dust event was transported to WYRDR at an altitude of <5 km, while the second transport height was at an altitude of <3 km. The first one was accompanied with the dry‐cold air mass in the northwest moving eastward and southward. By comparison, in the second event, the dust aerosols were mixed with anthropogenic aerosols from southwestern China. Meanwhile, as southerly warm‐humid air flows prevailed at near‐surface layer over the WYRDR in the second event, the associated higher relative humidity potentially induced hygroscopic growth of polluted dust aerosols, resulting in explosive growth of PM10 . In addition, the average depolarization ratio of aerosols over WYRDR on April 6 was 0.3, while on April 11 it was 0.2, indicating that the previous pollution event featured more obvious nonspherical characteristics of aerosols. Our findings provide scientific evidence that transboundary dust events and resultant local PM10 pollution are closely related to various transport trajectories of dust aerosols as well as the local vertical wind profiles and surface humidity conditions. Key Points: The magnitudes of local PM10 pollutions depend on various transport trajectories of dust aerosols as well as local meteorological conditions Different dust transported heights are revealed by integrated observations of satellite remote sensing and ground‐based lidar The spherical characteristics of dust‐related aerosols are identified by depolarization ratio of aerosols from lidar observation